Effect of nonlinear soil−structure interaction and lateral stiffness on seismic performance of mid−rise RC building - Firoj M.; Bahuguna A.; Kanth A.; Agrahari R. (My University, 2025)
In this study, the nonlinear soil-structure interaction (SSI) is considered to analyse the mid-rise structure's seismic performance with proportional lateral stiffness of columns in the orthogonal direction. The model's geometry is created using a finite element-based software package (ABAQUS). Cap plasticity and hysteretic models are used to mimic the nonlinear behaviour of soil and structural components, respectively. Truncated soil mass is incorporated using the spring and dashpot at the boundaries node with a MATLAB code for the dynamic analysis. The methodology validation is carried out on the shallow foundation under the cyclic loading and found in good agreement. Static pushover analysis of 4-storey, 8-storey mid-rise structures and 12-storey dual RC frame system is carried out to estimate the yielding displacement of the building structure at the roof level, which is further used in the incremental dynamic analysis (IDA) of the SSI and fixed base system. IDA is carried out for earthquake intensities ranging from 0.1g to 0.6g. IDA results are represented in terms of displacement ductility demand, normalised peak settlement, base shear, normalised peak foundation sliding and drift ratio. From the IDA analysis, the fragility assessment of the building is carried out for both the cases (fixed and SSI base). The present study concluded that lateral stiffness and SSI significantly affect the seismic performance of mid-rise buildings. © 2022 Elsevier Ltd